2017
DOI: 10.1108/ijbm-01-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Managing frontline employee performance through coaching: does selling experience matter?

Abstract: Purpose The impact of managerial coaching on frontline employee performance has received initial support in literature in recent years. However, no studies have explored if this impact should vary according to the career stage that the employee is in. If an interaction effect exists, then managers should expect different results when coaching people in different stages of their careers. Otherwise, all employees (independently of their career stage) can benefit from the positive impact of coaching and, thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 62 publications
3
33
0
1
Order By: Relevance
“…Although managerial and executive coaching are common in some aspects and both derived from one root (Hagen, 2012), research has identified these two streams as two distinct structures (D’Abate et al , 2003 Hagen,2012; Pousa, 2012), as well as these two streams, differ from other managerial behaviours such as monitoring, coordinating and providing feedback (Ingram et al , 2005; McLean et al , 2005; Pousa, 2012; Richardson, 2009). Recently, researchers have argued that managerial coaching is based on a high-quality exchange between coach and employee which leads to more open communication between them, higher levels of empowerment, and better working relationships (Onyemah, 2009; Pousa et al , 2017). This perspective on managerial coaching is especially important in the field of banking as it leads to the development of employee’s customer orientation (Pousa and Mathieu, 2014a), as well as customer-oriented behaviours leading to increased customer loyalty and Increasing banks’ competitive advantage (Bhat and Darzi, 2016).…”
Section: Literature Review and Research Backgroundmentioning
confidence: 99%
“…Although managerial and executive coaching are common in some aspects and both derived from one root (Hagen, 2012), research has identified these two streams as two distinct structures (D’Abate et al , 2003 Hagen,2012; Pousa, 2012), as well as these two streams, differ from other managerial behaviours such as monitoring, coordinating and providing feedback (Ingram et al , 2005; McLean et al , 2005; Pousa, 2012; Richardson, 2009). Recently, researchers have argued that managerial coaching is based on a high-quality exchange between coach and employee which leads to more open communication between them, higher levels of empowerment, and better working relationships (Onyemah, 2009; Pousa et al , 2017). This perspective on managerial coaching is especially important in the field of banking as it leads to the development of employee’s customer orientation (Pousa and Mathieu, 2014a), as well as customer-oriented behaviours leading to increased customer loyalty and Increasing banks’ competitive advantage (Bhat and Darzi, 2016).…”
Section: Literature Review and Research Backgroundmentioning
confidence: 99%
“…Karatepe and Aga’s (2013) past study in Northern Cyprus indicated that job resourcefulness activated FBEs’ job performance but it did not serve as a mediator between coworker support and job performance. Pousa et al ’s (2017) study conducted in Canadian banks indicated that managerial coaching fostered behavioral and sales performances. In a recent study of employees in an insurance company in China, there was no empirical support for sales orientation as a mediator between managerial coaching and job performance (Pousa et al , 2018).…”
Section: Literature Review Research Model and Hypothesesmentioning
confidence: 99%
“…Despite its significance, studies in the field of the banking industry are considerably lacking compared to those in other academic disciplines. Decision making in the banking industry has a high likelihood of forming biases due to heuristics in decision making because of uncertainty, complexity, ambiguity of policy goals and fallibility of information (Pousa et al , 2017). In particular, considering the ripple effect of a financial policy, it is crucial to conduct systematic research on whether heuristics and biases exist in the decision making processes of the policy makers who oversee financial decision making (Chen et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%